PELATIHAN PENINGKATAN NILAI TAMBAH JAGUNG DARI PENGOLAHAN HINGGA PEMASARAN DIGITAL BAGI KELOMPOK TANI HARAPAN JAYA DI DESA BALATA DUA PARBALAN - Sitorus, Peniel Sam Putra; Situmorang, Eduward; Sirait, Gloria; Sianipar, Vina; Adolf MS, Albert; Desmon Sirait, Glenn; Junita Arista Siringoringo, Kerin; Sitorus, Maria; Sitorus, Pontas (Nusantara Hasana Journal, 2025)
Simalungun Regency has 32 sub-districts covering an area of 438,660 hectares, representing 6.12% of the total area of North Sumatra province. There are 386 villages (nagori) and 27 sub-districts (kelurahan). In Pematang Bandar District, corn and rice are commonly cultivated. In Balata Village, Jorlang Hataran District, farmers are organized into the "Harapan Jaya" farmer group and prefer to cultivate corn. Corn prices in the Indonesian market are unstable, impacting farmers’ incomes. Training in processing corn into food is needed to increase their income. This training encompasses skills in production and marketing. Digital marketing training can help farmers promote their products and expand their marketing reach. Corn is an important commodity in Indonesia, serving as a source of food, animal feed, and industrial raw materials. Corn is also a staple food in some regions and is used in various industries. Corn mills are essential post-harvest tools to increase corn’s added value, improve production efficiency compared to manual methods, and support food security. However, many farmers in Indonesia still use traditional methods with low productivity and lack knowledge of crop processing and marketing strategies. Farmers face various challenges, such as limited access to information and price fluctuations. Capacity building through training is needed to improve production and marketing. The "Harapan Jaya" farmer group focuses on corn cultivation and sales, but has not yet maximized the added value of their harvest.